2022
DOI: 10.1371/journal.pone.0265520
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of salinity tolerance in wheat (Triticum aestivum L.)

Abstract: Understanding the genetics of salt tolerance is of utmost need to combat the rising prevalence of soil salinity through employing tolerant cultivars. The current study was carried out to investigate the quantitative genetic basis of agronomical and physiological-related traits of salinity-stressed plants using seven generations (parental cultivars, F1, F2, F3, BC1, and BC2) of wheat grown in the field under normal and saline conditions. The combined analysis of variance showed highly significant effects of sal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…To generate salinity-tolerant wheat genotypes, a selection procedure and genotypic variation are required [ 31 , 32 ]. However, the genetic basis of salt tolerance in wheat breeding is limited [ 22 , 33 , 34 ]. The shortage of genetic diversity restricts progress in improving wheat salt tolerance [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…To generate salinity-tolerant wheat genotypes, a selection procedure and genotypic variation are required [ 31 , 32 ]. However, the genetic basis of salt tolerance in wheat breeding is limited [ 22 , 33 , 34 ]. The shortage of genetic diversity restricts progress in improving wheat salt tolerance [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Salinity stress disrupts plant growth by increasing Na + ion assimilation and reducing the Na + /K + ratio, leading to osmotic stress and ion toxicity, consequently affecting normal plant development ( EL Sabagh et al., 2021 ). Additionally, under salinity stress, oxidative stress can impair plant growth through reduced photosynthetic capacity, oxidative damage caused by an imbalance in reactive oxygen species (ROS) production, and decreased antioxidant activity, ultimately leading to reduced crop yield ( Hasanuzzaman et al, 2014 ; Sadak, 2019 ; Omrani et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Radi et al [17] and Uzair et al [18] showed that salt stress caused a significant reduction in wheat PDW, with a more pronounced effect on salt-sensitive genotypes compared to salt-tolerant ones. Importantly, PDW and LA exhibit high heritability coupled with a high expected genetic gain from selection and are strongly associations with GY under salinity conditions [15,19,20]. Therefore, PDW and LA traits can serve as effective screening criteria for distinguishing salt-tolerant genotypes from salt-sensitive ones in real field conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Munns et al [3] found that the wheat lines with high levels of Na + lose chlorophyll at a faster rate compared to those with low Na + levels. In addition, Omrani et al [20] conducted a study using seven generations of wheat grown under normal and saline conditions in the field, and they reported a high broad-sense heritability for Chlt and SPAD values in saline conditions. Moreover, a strong positive correlation between Chlt and overall plant salinity tolerance was found in several field crops, including wheat, barley, rapeseed, and chickpea [22,23].…”
Section: Introductionmentioning
confidence: 99%